Dental Autotransplantation as a Rehabilitative Alternative in Young Patients: A Case Report - Medeiros, Andrezza Vital; Gonçalves Filho , Raimundo Thompson; Parente, José Lincoln Carvalho; Teixeira Neto, Murilo Alves; Pessoa, Hyago Marx Rodrigues; Lima, Adália Ribeiro (Brazilian Journal of Case Reports, 2026)
Dental autotransplantation (DAT) consists of the surgical transfer of a tooth from one site to another within the same patient, representing a biological, functional, and low-cost alternative for oral rehabilitation, especially in young patients still undergoing growth, in whom dental implants may be contraindicated. This study presents a case report of a 13-year-old female patient with impaction of teeth 46 and 47. After removal of tooth 46 and monitoring of bone healing, tooth 47 was found to be in a horizontal position with no possibility of proper eruption. Therefore, autotransplantation of tooth 47 into the alveolus of tooth 46 was indicated. The procedure was performed in a minimally traumatic manner, including preparation of the recipient socket, positioning of the tooth in slight infraocclusion, and stabilization with sutures. Clinical follow-up showed satisfactory healing, absence of infectious signs, and proper adaptation of the transplanted tooth. After one year and seven months of follow-up, tooth–alveolus integration, new bone formation, preserved pulp vitality, and absence of root resorption were observed, confirming the success of the treatment. The literature highlights that the success of DAT depends on factors such as atraumatic surgical technique, preservation of the periodontal ligament, short extraoral time of the donor tooth, imaging-based planning, and adequate post-transplant stability. Advantages of this method include preservation of alveolar bone, maintenance of dental space, possibility of orthodontic movement, and greater predictability in young patients, particularly when the donor tooth has incomplete root formation. It is concluded that dental autotransplantation, when properly indicated and performed, is a safe and effective alternative for oral rehabilitation in young patients, providing long-term functional, esthetic, and biological benefits.